Nighttime apple harvesting image enhancement based on a global–local feature fusion diffusion model - Liuchang Xu; Ting Ni; Fangshuo Zhou; Qingming Lin; Luyao Chen; Qianqian Luo; Kai Xia; Xingyu Xue; Xinyu Zheng; Sensen Wu; Zhenhong Du; Kai Fang; et al. (Computers and Electronics in Agriculture, 2026)

Octacosanol: Biological activities and bioavailability enhancement strategies - Liwen Liang; Xin yi Peng; Qiong Xiao; Feifei Zhong; Xiaoxi Zeng; Wen Li; Jing Deng; Qinlu Lin; Feijun Luo; Qingming Cao; Kilaza Samson Mwaikono (Food Chemistry, 2025)

A novel NIR iridium(III) complex-based probe for accurate imaging of mitochondrial biothiols in ferroptosis-mediated lung ischemia-reperfusion injury - Lin Jiang; Chaolong Liu; Wenyu Wang; Feng Li; Qingming Ma; Yong Sun (Analytica Chimica Acta, 2025)

Spatial mismatches and multi-dimensional conservation priorities for urban birds in China - Yunchun Ye; Wenpeng Lin; Jia Song; Qingming Wei; Yuanfan Zheng (Journal of Environmental Management, 2025)

Ocean acidification enhances the tolerance of dinoflagellate Prorocentrum donghaiense to nanoplastic-induced oxidative stress by modulating photosynthetic performance - Yue Zhu; Qingming Lin; Yao Yang; Yanmei Xia; Huidi Cai; Xucong Feng; Rodrigo J. Gonçalves; Wanchun Guan (Frontiers in Marine Science, 2024)
Introduction The impact of ocean acidification (OA) and nanoplastics (NPs) on harmful algal blooms (HAB) has emerged as a major global concern. However, the combined effects of OA and NPs on the HAB species are poorly understood. Methods In this study, dinoflagellate Prorocentrum donghaiense , a typical HAB species, was exposed to varying concentrations of NPs (108.15 ± 8.52 nm) (0, 5, 10, and 15 mg L −1 ) and CO 2 (low CO 2 : 417 ppm, pH: 8.00 and high CO 2 : 1045 ppm, pH: 7.73) for seven days to investigate the combined effects of OA and NPs. Results and discussion The findings revealed that NPs inhibited the growth of P. donghaiense by inducing oxidative stress, as indicated by elevated malondialdehyde (MDA) content and decreased carotenoid/chlorophyll-a ratio, even though photochemical efficiency (φ P0 , ψ 0 , and φ E0 ), rETR max and α were enhanced in response to NPs stress. However, OA promoted the growth and alleviated the adverse effects of NPs on P. donghaiense by increasing photochemical efficiency (φ P0 , ψ 0 , and φ E0 ) and energy flux (RC/CS 0 , TR 0 /CS 0 , ET 0 /CS 0 ) and enhancing the antioxidant ability (increased superoxide dismutase, and decreased MDA). P. donghaiense showed enhanced tolerance to NPs under simulated OA conditions. These findings enhance our knowledge of the HAB species response to NPs pollution under future OA scenarios.

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

3D/2D MnO/MXene heterostructure with high efficiency for adsorbing uranium - Chao Zhang; Yi Wang; Yi-Lin Liu; Qingming Zeng; Yanjun Wen; Lulin Guo; Haodong Chen; Xinyi Xie; Qingyi Zeng (Chemical Engineering Journal, 2024)

A self-driven solar coupling system with TiO2@MXene cathode for effectively eliminating uranium and organics from complex wastewater accompanying with electricity generation - Lulin Guo; Yi-Lin Liu; Qingming Zeng; Chao Zhang; Yanjun Wen; Qingyan Zhang; Guolong Tang; Qingsong Zhang; Qingyi Zeng (Journal of Hazardous Materials, 2024)

Synergistically adsorbing and reducing Uranium from water by a novel nano zero-valent copper/MXene 0D/2D nanocomposite - Yi-Lin Liu; Chao Zhang; Lulin Guo; Qingming Zeng; Rongzhong Wang; Haodong Chen; Qingyan Zhang; Qingyi Zeng (Water Research, 2023)

Solar-driven wastewater treatment coupled with hydrogen and electricity production via a bismuth-doped TiO2 nanorod array - Beibei Gao; Jing Tan; Yuhan Cao; Qingsong Zhang; Yanjun Wen; Qingming Zeng; Guolong Tang; Junwen Lv; Lin Wang; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2023)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Dysfunction of chaperone-mediated autophagy in human diseases - Zhaozhong Liao; Bin Wang; Wenjing Liu; Qian Xu; Lin Hou; Jinlian Song; Qingming Guo; Ning Li (Molecular and Cellular Biochemistry, 2021)

Contamination assessment, health risk evaluation, and source identification of heavy metals in the soil-rice system of typical agricultural regions on the southeast coast of China - Yanjun Ren; Meng Lin; Qingming Liu; Zhonghao Zhang; Xufeng Fei; Rui Xiao; Xiaonan Lv (Environmental Science and Pollution Research, 2021)

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

Visualizing DC morphology and T cell motility to characterize DC-T cell encounters in mouse lymph nodes under mTOR inhibition - Qiaoya Lin; Zheng Liu; Meijie Luo; Hao Zheng; Sha Qiao; Chenlu Han; Deqiang Deng; Zhan Fan; Yafang Lu; Zhihong Zhang; Qingming Luo (Science China Life Sciences, 2019)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

QTL analysis of floral traits of rice (Oryza Sativa L.) under well-watered and drought stress conditions - Hu Songping; Zhou Ying; Zhang Lin; Zhu Xudong; Wang Zhenggong; Li Lin; Luo Lijun; Zhou Qingming (Genes & Genomics, 2009)